Split-split plot design analysis, in exploring the efficacy of plants as natural measures, (biocides) of maize stem borer control - Ziwakaya, Paul Kundai (Midlands State University, 2017)
In this paper, comparison between the use of botanical methods of pest control and dipterex 25% grounded in controlling maize stem borer was done. An experiment was carried out at Midlands State University main campus during the rainy season of 2015-2016. A split-split plot design was used with two nitrogen levels as whole plot factor (0kg/ha and 100kg/ha), two varieties of maize as subplot factor (SC627 SeedCo and Pioneer 30G95) and six treatments of maize stem borer control methods as sub-subplot factor (lantana camara leaves extract, lantana camara flowers extract, euphorbia flesh extract, euphorbia fruit extract, dipterex 25% granular, and a control with nothing applied). Model assumptions diagnostic checking was performed and all the assumptions were satisfied. Analysis was done using Genstat version 14 and the results showed that all the biocides perform better with lantana leaves being the most effective. Interactional effect of nitrogen (100kg/ha), maize variety (Pioneer 30G95) and lantana leaves was an effective combination that includes botanical methods of pest control.